Geopolitical Impact of the Treaty of Lausanne on Iraqi Kurdistan (A Study in Political Geography) - مصطفى, أ.د. فؤاد حمه خورشيد; كريم, م.م. أكو أحمد (Sulaimani Journal for Humanities, 2025)
The changing of power balance around Kurdistan, especially after the emergence and strengthening of the nationalist Turks, after the Treaty of Sevres in 1920, forced the Allies to prepare for a new agreement with the Turks, the Treaty of Lausanne, which was signed and came into force on July 24, 1923. The agreement not only destroyed the roadmap of the Treaty of Severs for the establishment of the Kurdistan state, but also divided Kurdistan on to three states (Turkey, Syria and Iraq), thus dividing Kurdistan into four parts. The treaty did not mention the Kurdish rights. What was mentioned about Kurdistan was only the fate and ownership of Mosul province, which would be placed on the newly formed state (Turkey or Iraq). In Mosul, although the Kurds constituted the absolute majority of the population (65%), but without the will of the majority, the province was placed on the newly formed Iraqi state. All this was the result of a number of state interests and some domestic and international factors that occurred at that time, the most important of which was the richness of Mosul in oil, which caused the greed of the powerful states, especially (Britain and France) who worked to maintain their dominance in the region.
Keywords: Lausanne Treaty; South Kurdistan; Nationalist Turks; UK; Iraq